Glass in Building : Principles, Applications, Examples - Härth, Kristina; Tasche, Silke; Unnewehr, Stefan (Birkhäuser, 2012)
"Glass in Building" offers a compact and illustrated overview of the material-appropriate use of glass in building construction and provides information on designing with glass and producing and using specialized glass products, as well as on the building and planning regulations that must be taken into account when constructing with glass.